Shakespeare's stories. Histories - Birch, Beverley; Green, Robina; Shakespeare, William, 1564-1616. (New York : P. Bedrick Books, 1988)
Presents the stories of five of Shakespeare's plays: Antony and Cleopatra, Richard III, Henry IV, Henry V, and Julius Caesar.
Keywords: Shakespeare, William, -- 1564-1616 -- Histories -- Adaptations -- Juvenile literature; Shakespeare, William, -- 1564-1616 -- Stories, plots, etc. -- Juvenile literature; Shakespeare, William, -- 1564-1616 -- Adaptations